Congenital Short-Bowel Syndrome Is Associated With a Novel Deletion Mutation in the CLMP Gene: Mutations in CLMP Caused CSBS - Ou, Fen-fen; Li, Ming-jie; Mei, Li-bin; Lin, Xin-Zhu; Wu, Yan-an (Frontiers in Pediatrics, 2022)
Objective: To describe the clinical presentation and novel mutation in the coxsackie and adenovirus receptor-like membrane protein (CLMP) gene in a Chinese family with congenital short bowel syndrome (CSBS). Methods: We collected clinical data from a Chinese family with inherited CSBS, and performed whole exon sequencing of the children and their parents. The pathogenic sites of candidate genes were targeted, and the detected exon deletions were verified by quantitative PCR. Results: Two siblings in this family presented with bilious vomiting, and were diagnosed with CSBS on laparotomy. Two siblings and their parents underwent complete exome sequencing of the peripheral blood. Both children had CLMP gene exons 3–5 homozygous deletion mutation, while the parents had a heterozygous mutation. Conclusion: This study identified a novel mutation of the CLMP gene in a Chinese family with CSBS. Identification of this mutation can help with genetic counseling and prenatal diagnosis of CSBS.